A minissérie televisiva de Luiz Fernando Carvalho: estudo de caso: Hoje é dia de Maria - Miranda, Bionathi Borges Dias de (2010)
This research aims to study the minisseries, taking as exemplary case the work of Luis Fernando Carvalho and especially Hoje é dia de Maria in 2007. We start with an overview of fairy tales, since such miniseries constitutes a mosaic of them. In this section we emphasize the presentation of the child in this game to all the tales and we analyzed some of these stories, according to the psychoanalysis. We developed also a history of soap operas, with emphasis on the role of the Rede Globo TV in the process of popularization of gender. We ending with this situation studied Hoje é dia de Maria, who develops a semiotic analysis of some of the symbols with which the narrative works: a key, the bird, the wheel